Emigracja blues - Sieranska-Syta, Katarzyna (Warszawa : Polska Oficyna Wydawnicza "BGW", 1994)
Memoirs of a Polish immigarant to Australia.
Keywords: Sieranska-Syta, Katarzyna; Sieranska-Syta, Katarzyna -- Travel; Polish people -- Australia -- Biography; Immigrants -- Australia -- Biography